Assessing thiamethoxam environmental distribution in successively cultivated corn: insights from drainage lysimeter and laboratory studies - Affonso Celso Gonçalves Junior; Elio Conradi Junior; Daniel Schwantes; Angélica de Fatima Bortolato Piccioli; Deonir Secco (Revista Brasileira de Recursos Hídricos)
ABSTRACT The insecticide thiamethoxam (TIA) is commonly used in soybean and corn rotation systems, raising concerns about its environmental impact amid climate change. This study evaluated TIA mobility in Oxisol using percolation lysimeter, focusing on the transport by runoff and percolation, as well as the retention and dissipation in the soil. Simulated precipitation (150 mm h−1) was applied 24 and 48 hours post-application at a recommended dose of 0.25 L ha−1 during the 2020/2021 season. Laboratory analyses assessed TIA sorption and dissipation, using UPLC-DAD for quantification and categorizing soil samples into calcined and uncalcined treatments. Freundlich isotherms indicated irreversible sorption in calcined samples and cooperative adsorption in uncalcined ones. Thermodynamic analysis showed endothermic adsorption in uncalcined samples and exothermic processes in calcined ones, with spontaneous adsorption behavior. Notably, no TIA was detected in water or soil residues, likely due to low organic matter and dilution from rainfall. However, substantial TIA levels were found in foliar tissues, indicating efficient plant absorption. These findings highlight the rapid uptake of TIA by plants and the potential risks from intense rainfall that could lead to soil erosion and water contamination. Further research is needed to evaluate TIA's environmental impacts, particularly concerning its metabolites.